O deus na ampulheta: o imaginário do medo em torno do tempo na poesia de Roberto Pontes - Miranda, Leonildo Cerqueira (2025)
This dissertation examines two poetic works by Roberto Pontes, Lições de Tempo and Os Movimentos de Cronos, published in a single volume in 2012. The collection of images employed by Pontes to compose his texts points to conceptions of time that relate to notions of transience, destruction, omnipotence, and death. In both works, these conceptions are expressed through symbols, archetypes, and aesthetic and linguistic devices, such as the seasons of the year, the roughness of the skin as a sign of aging, the skeleton wielding the scythe, the enigmatic sphinx poised to devour its victims, and the metaphors and allegories used for symbolic elaboration and personified masking. All of this is structured around two principal topoi linked to the Horatian tradition of the topical genre of Carpe diem: tempus fugit, or time flees, and persona temporis, or the personification of time, a topical form proposed in this research based on the identification of this recurring device in the works of Roberto Pontes and other artistic manifestations. Embedded in these ways of conceptualizing the temporal category lies a mental trace of fear, as the passage of time works as a catalyst for transformation and destruction of being, propelling it constantly and uninterruptedly toward annihilation. Thus, the fear of time is ultimately the fear of death. Recognizing this, the thesis to be developed is as follows: the works of Roberto Pontes reflect a residual imaginary of fear surrounding the matter of time, as time signifies finitude and death. To analyze and demonstrate this imaginary in Pontes's texts, a comparative investigative method was employed, combined with the Theory of Residuality, highlighting how the temporal element has been conceptualized by various peoples, philosophers, artists, and scientists throughout the centuries. This approach establishes an entire Western tradition on the theme, fostering the formation of a collective imaginary regarding temporality. The theoretical framework enabling the analyses and supporting the arguments about time includes authors such as Plato (2011), Aristotle (1995), Saint Augustine (2002), Bergson (2020), Heidegger (2015), Rovelli (2018), and Pimenta (2021). For the conceptual discussions concerning imaginary and fear, the studies of Durand (2012), Jung (2014), Wunenburger (2007), Espig (2004), Bauman (2022), and Delumeau (2009) were utilized. In the field of residuality, the works of Martins (2015), Torres (2016), Leitão (2018), and Pontes (2020) were particularly prominent.